Mechanical and Dynamic Mechanical Characterization of Epoxy Composites Reinforced with Casuarina Leaf Bio Fibre - Suja, R. Nalini; Sridevi, B.; Kumar Thiagamani, Senthil Muthu (Journal of Research Updates in Polymer Science, 2024)
This study investigates the influence of casuarina leaf biofibre on the mechanical and morphological characteristics of epoxy resin composites. Composites were prepared using the hand-layup method, incorporating varying volume fractions of the biofibre (4%, 8%, 12%, 16%, 20% and 24% v/v). Mechanical and dynamic mechanical tests were carried out to assess the impact of the biofibre on the composite material. Mechanical testing revealed significant enhancements in tensile strength of 29.2 MPa, particularly at a biofibre volume fraction of 12% and the composite with the highest impact and flexural strengths measured at 2621 J/m2 and 41.1 MPa, respectively for the 16%v/v fibre loading. Dynamic mechanical analysis (DMA) results demonstrated improved viscoelastic properties attributed to the presence of the biofibre. Scanning electron microscopy (SEM) examination of tensile tested samples provided insights into interfacial bonding and filler dispersion within the composite matrix. Overall, the findings highlight the potential of casuarina leaf biofibre to enhance specific mechanical properties and viscoelastic behaviour of epoxy casuarina composites. Optimizing the biofibre volume fraction offers possibility to tailor composite properties for specific application requirements. This research advances the development of bio-based composite materials, contributing valuable insights for the creation of sustainable and high-performance engineering materials.